Oxford urdu silsila "Hans" (for class 5) - Amina Azfar (Oxford University Press Oxford, 1999)
"Hans" by Amina Azfar is a heartwarming and reflective story that explores the emotional journey of its characters, emphasizing the importance of joy, resilience, and finding happiness amidst life's challenges.